Comparison of long-pulsed alexandrite laser and topical tretinoin-ammonium lactate in axillary acanthosis nigricans: A case series of patients in a before-after trial - Amirhoshang Ehsani; Pedram Noormohammadpour; Azadeh Goodarzi; Mostafa Mirshams-Shahshahani; Seyyed-Pardis Hejazi; Elham-Sadat Hosseini; Arghavan Azizpour (Babol University of Medical Sciences, 2016)
Background: Acanthosis nigricans (AN) is a brown to black, velvety hyperpigmentation of the skin that usually involves cutaneous folds. Treatment of AN is important regarding cosmetic reasons and various therapeutic modalities have been used for these purposes. The goal of this study was to compare the effectiveness of long-pulsed alexandrite laser and topical tretinoin-ammonium lactate for treatment of axillary-AN. Methods: Fifteen patients with bilateral axillary-AN were studied in Razi Hospital, Tehran, Iran. Diagnosis was confirmed by two independent dermatologists. Each side skin lesion was randomly allocated to either topical mixed cream of tretinoin 0.05%- ammonium lactate 12% or long-pulsed alexandrite laser. Duration of treatment was 14 weeks. At endpoint, the mean percent reduction from baseline in pigmentation area was compared between the two groups. Results: The study population consisted of 15 patients, three males and 12, females. The mean age of patients was 28.5±4.9 years. The mean percent reduction was 18.3±10.6%, in tretinoin/ammonium lactate group and 25.7±11.8% in laser group (P=0.004). Conclusion: These findings indicate that the application of alexandrite laser is a relative effective method for treatment of axillary-AN. However, this issue requires further studies with prolonged follow-up period.